2015
DOI: 10.1186/s12866-015-0588-0
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of Myriocin on clinically relevant Aspergillus fumigatus strains producing biofilm

Abstract: BackgroundThe human pathogenic mold Aspergillus fumigatus is able to form a complex biofilm embedded in extracellular matrix. Biofilms confer antimicrobial resistance and it is well known that aspergillosis is often refractory to the conventional antifungal therapy. The treatment of biofilm-related infections poses a significant clinical challenge on a daily basis, promoting the search for new therapeutic agents.Our aim was to exploit the modulation of sphingolipid mediators as new therapeutic target to overco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…Although this step is conserved between mammalian and fungal sphingolipids biosynthesis, the use of myriocin has significantly contributed to understand the importance of sphingolipids in fungi [91]. Myriocin treatment against Candida and Aspergillus species impairs biofilm formation through inhibition of sphingolipid formation, leading to changes in lipid rafts distribution in fungal membranes and cell morphology [92,93]. Nevertheless, since …”
Section: Targeting the Biosynthesis Of Fungal Sphingolipidsmentioning
confidence: 99%
“…Although this step is conserved between mammalian and fungal sphingolipids biosynthesis, the use of myriocin has significantly contributed to understand the importance of sphingolipids in fungi [91]. Myriocin treatment against Candida and Aspergillus species impairs biofilm formation through inhibition of sphingolipid formation, leading to changes in lipid rafts distribution in fungal membranes and cell morphology [92,93]. Nevertheless, since …”
Section: Targeting the Biosynthesis Of Fungal Sphingolipidsmentioning
confidence: 99%
“…Both compounds had MICs of 50 μg/ml against C. albicans , only Candidamide A ( 32 ) was active against A. niger (MIC 20 μg/ml), whereas out of the two, only Candidamide B ( 33 ) inhibited T. rubrum growth (MIC 40 μg/ml) (Wu et al, ). Precedence for the antifungal activities of ceramide compounds exists in the literature (Perdoni et al, ). For example, the commercial sphingolipid synthesis inhibitor Myriocin in Aspergillus fumigatus cultures exhibited a minimum effective concentration of 8 μg/ml (Perdoni et al, ).…”
Section: Antifungal Activities Of Isolatesmentioning
confidence: 99%
“…Myriocin acts by strong inhibition of serine palmitoyltransferase, a key enzyme in the synthesis of sphingolipids [73]. It has been demonstrated that C. albicans biofilms possess a higher ratio of sphingolipids than planktonic cells, and accordingly, treatment with myriocin completely prevented the formation of C. albicans biofilms [74], as well as biofilms of Aspergillus fumigatus clinical isolates [75]. Although these reports are rather optimistic, one should keep in mind that myriocin is toxic for eukaryotes and has a small therapeutic window.…”
Section: Fungal Metabolites Of Polyketide Origin For Biofilm-controlmentioning
confidence: 99%